Relation between cognitive impairment and treatment adherence in elderly hypertensive patients - Chudiak A (Clinical Interventions in Aging, 2018)
Anna Chudiak,1 Izabella Uchmanowicz,1 Grzegorz Mazur2 1Department of Clinical Nursing, Faculty of Health Sciences, Wroclaw Medical University, Wrocław, Poland; 2Department and Clinic of Internal and Occupational Diseases and Hypertension, Wroclaw Medical University, Wrocław, Poland Background: Nonadherence to medical treatment and lack of cooperation in hypertensive patients >65 years of age are believed to be caused by a number of age-related problems, such as cognitive impairment. Numerous epidemiological and prospective studies have demonstrated that hypertension that remains untreated for many years or is unsuccessfully treated for reasons such as poor compliance and adherence of the patient may lead to cognitive impairment. Objective: The objective of this study was to investigate the occurrence of cognitive impairment and its effect on treatment compliance and adherence in elderly hypertensive patients. Design: This study was an analytical cross-sectional study. Patients and methods: The study was conducted on 300 patients aged 65–91 years (mean age=71.8 years, SD=7.8 years) diagnosed with hypertension. The following research tools were used: 1) Hill-Bone High Blood Pressure Compliance Scale (HBCS) and 2) Mini–Mental State Examination (MMSE). We also analyzed medical documentation to obtain basic sociodemographic and clinical data. The study was approved by the Bioethics Committee of the Medical University of Wroclaw (no KB-144/2016). Results: Cognitive impairment occurred in 60% of the patients. A group of 63% patients complied with antihypertensive therapy, with the mean score of 20.8 points. Cognitive impairment was strongly correlated with the total score of the HBCS questionnaire (p<0.001) and two of its subscales: “appointment keeping” (p<0.001) and “medication taking” (p<0.001). Conclusion: Compliance and adherence levels are higher in patients with a higher educational level, whereas male sex adversely affects treatment adherence in elderly hypertensive patients. Keywords: cognitive impairment, compliance, hypertension, old age, treatment adherence